Oil Wealth and Development in Uganda and Beyond Prospects, Opportunities, and Challenges - Langer, Arnim; Ukiwo, Ukoha; Mbabazi, Pamela (Leuven University Press, 2019)
Large quantities of oil were discovered in the Albertine Rift Valley in Western Uganda in 2006. The sound management of these oil resources and revenues is undoubtedly one of the key public policy challenges for Uganda as it is for other African countries with large oil and/or gas endowments. With oil expected to start flowing in 2021, the current book analyses how this East African country is preparing for the challenge of effectively, efficiently, and transparently managing its oil sector and resources. Adopting a multidisciplinary, comprehensive, and comparative approach, the book identifies a broad scope of issues that need to be addressed in order for Uganda to realise the full potential of its oil wealth for national economic transformation. Predominantly grounded in local scholarship and including chapters drawing on the experiences of Nigeria, Ghana, and Kenya, the book blazes a trail on governance of African oil in an era of emerging producers. Oil Wealth and Development in Uganda and Beyond will be of great interest to social scientists and economic and social policy makers in oil-producing countries. It is suitable for course adoption across such disciplines as International/Global Affairs, Political Economy, Geography, Environmental Studies, Economics, Energy Studies, Development, Politics, Peace, Security and African Studies.